Analisis Kemampuan Berpikir Tingkat Tinggi Menurut Teori Anderson dan Krathwohl Pada Siswa Kelas VII SMPN 25 Padang - Niken Septia Ningsih; Yusri Wahyuni; Fauziah Fauziah; Rita Desfitri (IAIN BENGKULU, 2022)
This research was motivated by the low ability of high-level thinking of students. In addition, the results of the student math midterm exam are still much less than KKM scores. This research aims to analyze the high-level thinking skills of students of class VII SMPN 25 Padang according to Anderson and Krathwohl Theory and describe the factors that affect the high-level thinking ability of students of class VII SMPN 25 Padang. This type of research is descriptive research, the population in this study is the entire student of class VII SMPN 25 Padang. Sampling is based on purposive sampling technique with sample class VII1 numbering 30 people. The instruments used in this study were description and interview tests. The results showed that the high-level thinking skills of students of class VII SMPN 25 Padang were divided into three, namely high, medium and low. The high-level thinking ability of high group students was 10%, the moderate group was 73.33%, and the low group was 16.67%. Factors that affect students' high-level thinking skills are not yet skilled in understanding problems, the ability to remember the subject matter of some students is still low, the ability of students to make strategies in answering is still low due to lack of problem training at home, students tend to quickly give up, class conditions are less calm during learning and some students admit to rarely learning and repeating lessons at home. From the results of the research conducted, the ability to think high level students include enough categories, this can be seen in grouping the percentage of high-level thinking skills of students. From the results of the study it is recommended that teachers understand the weaknesses and strengths of each student's thinking skills, because students have different thinking skills, especially high-level thinking skills.Keywords: Anderson and Krathwohl, high-level thinking skills, analyze, evaluate